Penetrating Abdominal Injury by a Large Stone. - Chandrashekhar C Mahakalkar (Online Journal of Health & Allied Sciences, 2012)
Penetrating trauma can be commonly caused by sharp objects. We report a case of penetrating injury of abdomen caused by a fairly large sized stone which is used for sharpening the objects or weapons. It pierced through the abdominal wall musculature and caused ileal transection, mesenteric tear and gastric perforation.